2010
DOI: 10.1016/j.jacc.2009.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclosporine on Left Ventricular Remodeling After Reperfused Myocardial Infarction

Abstract: Cyclosporine used at the moment of acute myocardial infarction reperfusion persistently reduces infarct size and does not have a detrimental effect on LV remodeling. These results are preliminary and must be supported by further studies. (Ciclosporin A and Acute Myocardial Infarction; NCT00403728).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(126 citation statements)
references
References 17 publications
1
121
0
4
Order By: Relevance
“…Importantly, our data were in agreement with those reported by Piot et al, 5 who carried out a well-designed pilot study of CsA in patients with ST-segment elevation AMI, and demonstrated smaller infarct sizes after percutaneous coronary intervention, which was confirmed by DE-MRI. Mewton et al 21 recently confirmed that CsA-induced reduction in infarct size was associated with a lower left ventricle dilatation at day 5, which was maintained at 6 months.…”
mentioning
confidence: 84%
“…Importantly, our data were in agreement with those reported by Piot et al, 5 who carried out a well-designed pilot study of CsA in patients with ST-segment elevation AMI, and demonstrated smaller infarct sizes after percutaneous coronary intervention, which was confirmed by DE-MRI. Mewton et al 21 recently confirmed that CsA-induced reduction in infarct size was associated with a lower left ventricle dilatation at day 5, which was maintained at 6 months.…”
mentioning
confidence: 84%
“…A total of 5 RCTs, which had been published in peer-reviewed journals, were included in our studies [19][20][21][22][23][24]. We extracted the baseline study details from all the selected trials (Tables 2, 3); outcomes not included in the analysis are listed in Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…In a subgroup analysis, a similar reduction in infarct size was demonstrated on day 5 with cardiac magnetic resonance imaging (CMR). In a follow-up study, Mewton et al [78] found that this infarct-sparing effect of cyclosporine was persistent at 6 mo. However, in a more recent study, no effect was shown of early cyclosporine administration as an adjunct to thrombolysis in STEMI patients in relation to infarct size, left ventricular function, heart failure or death [65] .…”
Section: Pharmacological Conditioningmentioning
confidence: 97%